2016
DOI: 10.3168/jds.2015-10072
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical evaluation of sheep milk yogurts containing different levels of inulin

Abstract: The present study aimed to evaluate the physicochemical parameters of sheep milk yogurt smoothies (SMY) containing inulin at different levels (0, 2, 4, and 6%). Titratable acidity and pH, yogurt bacteria counts, fatty acids profile, and healthy lipid indices were evaluated during 28 d of refrigerated storage. As expected for yogurts, Streptococcus thermophilus counts decreased 1 to 3 log cycles and Lactobacillus delbrueckii ssp. bulgaricus counts decreased 1 to 2 cycles from d 1 to 28. The protective effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 45 publications
3
40
1
Order By: Relevance
“…The polyunsaturated fatty acids (PUFAs) in sheep milk fat comprise linoleic (cis-9, cis-12 C18:2) and α-linolenic (cis-9, cis-12, cis-15 C18:3) acids, as well as smaller concentrations of their isomers [19]. Mono- and polyunsaturated FA in sheep milk may contribute to the prevention of cardiovascular diseases owing to their atherogenic and thrombogenic indixes [20,21]. Among ruminants, sheep milk fat contains not only one of the highest levels of conjugated linoleic acid (0.65 g CLA/100 g of FA) but also a large amount of vaccenic acid, its physiological precursor [22].…”
Section: Introductionmentioning
confidence: 99%
“…The polyunsaturated fatty acids (PUFAs) in sheep milk fat comprise linoleic (cis-9, cis-12 C18:2) and α-linolenic (cis-9, cis-12, cis-15 C18:3) acids, as well as smaller concentrations of their isomers [19]. Mono- and polyunsaturated FA in sheep milk may contribute to the prevention of cardiovascular diseases owing to their atherogenic and thrombogenic indixes [20,21]. Among ruminants, sheep milk fat contains not only one of the highest levels of conjugated linoleic acid (0.65 g CLA/100 g of FA) but also a large amount of vaccenic acid, its physiological precursor [22].…”
Section: Introductionmentioning
confidence: 99%
“…Balthazar et al . () found that inulin added in prebiotic sheep milk yoghurt decreases samples post‐acidification while short‐chain fatty acids (SCFA) or polyunsaturated fatty acids (PUFA) were not affected by fibre (inulin) addition. Medium‐ and long‐chain fatty acids and monounsaturated fatty acids in prebiotic sheep milk yoghurt increased shelf life period.…”
Section: Inulin Sensorial Aspectsmentioning
confidence: 99%
“…To increase the therapeutic value of yoghurt, it has also been prepared using sheep milk (Balthazar et al . ). Esmerino et al .…”
Section: Introductionmentioning
confidence: 97%